A carbon fiber reinforced low-density flame-retardant polyethylene cable material and preparation method thereof

By using modified carbon fiber and modified linear low-density polyethylene in polyethylene cable materials, the interfacial compatibility and adhesion of the material are enhanced, and the problem of degradation of polyethylene material performance under high inorganic flame retardant dosage is solved, and the impact strength, tensile strength and electrical performance of the material are improved.

CN116285078BActive Publication Date: 2025-03-14HANGZHOU KEJIA NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310263337.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-03-14
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

Under the conditions of high inorganic flame retardant dosage, the impact strength, tensile strength and electrical properties of polyethylene materials have all declined, making it difficult to meet the mechanical and electrical properties improvement needs of the cable industry.

Method used

Carbon fiber reinforced low-density flame-retardant polyethylene cable material is used to improve the interface compatibility and interface adhesion between the modified carbon fiber and the matrix resin through the combination of modified linear low-density polyethylene, thereby improving the impact strength, tensile strength and electrical properties of the material.

Benefits of technology

The impact strength, tensile strength and electrical properties of polyethylene materials have been significantly improved, and the problem of material performance degradation under high flame retardant dosage is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004132150930000021
    Figure BDA0004132150930000021
  • Figure BDA0004132150930000061
    Figure BDA0004132150930000061
  • Figure BDA0004132150930000062
    Figure BDA0004132150930000062
Patent Text Reader

Abstract

The present application discloses a carbon fiber reinforced low-density flame-retardant polyethylene cable material and a preparation method thereof, wherein the cable material comprises the following raw materials in mass fractions: 60-80 parts of linear low-density polyethylene, 20-40 parts of modified linear low-density polyethylene, 20-38 parts of flame retardant, 3-8 parts of toughening agent, 1-4 parts of antioxidant, 1-3 parts of lubricant, 2-6 parts of silicone masterbatch, 2-5 parts of carbon black, and 5-8 parts of modified carbon fiber; the surface of the modified carbon fiber is attached with isocyanate groups and ethylene segments, and maleic anhydride is grafted on the molecular chain of the modified linear low-density polyethylene. The polyethylene cable material of the present application still maintains excellent electrical properties, tensile strength and impact strength at a high flame retardant dosage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of cable materials, and in particular to a carbon fiber reinforced low-density flame-retardant polyethylene cable material and a preparation method thereof. Background Art

[0002] Polyethylene materials have excellent wear resistance, weather resistance and chemical resistance, so they are widely used in today's wire and cable industry. However, polyethylene itself does not have flame retardant properties, and flame retardants need to be added during the application process to improve the flame retardant performance of the material and thus improve the fire safety of the material. Commonly used flame retardants can be divided into organic flame retardants represented by bromine and nitrogen series, and inorganic flame retardants represented by magnesium hydroxide, aluminum hydroxide, and antimony trioxide. Organic flame retardants have excellent flame retardant effects, but with the country and the international community paying more attention to environmental protection, organic flame retardants will produce harmful gases when burned that can cause damage to the human body, so environmentally friendly inorganic flame retardants are increasingly favored by polyethylene cable manufacturers.

[0003] However, in the production process, in order to meet the corresponding flame retardant requirements, the amount of inorganic flame retardants added is very large, which leads to a significant decrease in the impact strength, tensile strength and electrical properties of the material. The use of inorganic flame retardants and phosphorus nitrogen flame retardants can effectively reduce the amount of flame retardants and improve the impact strength and tensile strength of the material, but the electrical properties of the material are not significantly improved. Therefore, under the condition of high inorganic flame retardant dosage, how to improve the mechanical and electrical properties of polyethylene materials is an urgent issue in the cable industry. Summary of the invention

[0004] In order to solve the problem of decreased impact strength, tensile strength and electrical properties of polyethylene under high flame retardant dosage, the present application provides a carbon fiber reinforced low-density flame retardant polyethylene cable material and a preparation method thereof.

[0005] In the first aspect, the present application provides a carbon fiber reinforced low-density flame-retardant polyethylene cable material, which includes the following raw materials in parts by weight: 60 to 80 parts of linear low-density polyethylene, 20 to 40 parts of modified linear low-density polyethylene, 20 to 38 parts of flame retardant, 3 to 8 parts of toughening agent, 1 to 4 parts of antioxidant, 1 to 3 parts of lubricant, 2 to 6 parts of silicone masterbatch, 2 to 5 parts of carbon black, and 5 to 8 parts of modified carbon fiber; the surface of the modified carbon fiber is attached with isocyanate groups and ethylene segments, and the modified linear low-density polyethylene molecular chain is grafted with maleic anhydride.

[0006] By adopting the above technical solution, the addition of modified carbon fiber enhances the impact strength, tensile strength and electrical properties of the material. On the one hand, the modified carbon fiber is attached with isocyanate groups. During the melt processing, the isocyanate groups will capture the active H atoms of maleic anhydride on the modified linear low-density polyethylene molecular chain, so that chemical cross-linking occurs between the modified carbon fiber and the matrix resin; on the other hand, the surface of the modified carbon fiber is attached with ethylene segments. According to the principle of similar dissolution of polymers, the ethylene segments and the segments of the matrix resin interpenetrate and diffuse with each other. Through these two aspects, the interface wettability between the carbon fiber and the matrix resin can be effectively improved, and the interface adhesion can be improved, so that the modified carbon fiber can effectively act on the matrix resin, and improve the impact strength, tensile strength and electrical properties of the polyethylene material.

[0007] Preferably, the surface of the modified carbon fiber is coated with a sizing agent, and the sizing agent includes a latent crosslinking agent X-NCO, an aqueous polyethylene wax emulsion and a dispersant in a mass ratio of (1-7):(1-6):0.1.

[0008] More preferably, the mass ratio of the latent crosslinking agent X-NCO, the aqueous polyethylene wax emulsion and the dispersant is 5:5:1.

[0009] Preferably, the dispersant is selected from butanone, acetone or a combination thereof.

[0010] The molecular structure of the latent crosslinking agent X-NCO is:

[0011]

[0012] Where X represents an aliphatic capping end.

[0013] The sizing agent uses aqueous polyethylene wax emulsion as a binder to coat the latent crosslinking agent X-NCO on the surface of the carbon fiber. The dispersant allows the latent crosslinking agent X-NCO to be more evenly dispersed in the aqueous polyethylene wax emulsion. The aqueous polyethylene wax emulsion is a low molecular weight polyethylene with a low degree of polymerization and a short molecular chain, which can introduce isocyanate groups and ethylene segments on the surface of the carbon fiber, effectively improving the interface wettability between the carbon fiber and the matrix resin.

[0014] The latent crosslinking agent X-NCO can also be used as a binder in emulsions such as water-based polyurethane emulsions, but the lack of participation of ethylene segments is not conducive to improving the compatibility of carbon fibers and matrix resins.

[0015] Preferably, the modification steps of the modified carbon fiber include: carbon fiber desizing: the carbon fiber is desizing in an inert gas atmosphere; carbon fiber sizing: the desizing carbon fiber is subjected to impregnation sizing, drying and compacting, and shaping and cutting to obtain the modified carbon fiber.

[0016] The carbon fiber sold on the market is coated with a layer of epoxy resin sizing agent on the surface to protect it from damage during transportation and to allow it to have a better wetting effect with other materials. However, the epoxy resin sizing agent will affect the compatibility of the carbon fiber with linear low-density polyethylene. Therefore, the carbon fiber must be modified and desized first.

[0017] Preferably, in the carbon fiber desizing process, the desizing temperature is 500-600°C.

[0018] Preferably, the sizing rate of the modified carbon fiber is 0.5%-5%, and the sizing rate is the percentage of the sizing agent on the surface of the carbon fiber to the mass of the carbon fiber.

[0019] Preferably, the length of the modified carbon fiber is 1 mm-10 mm, more preferably 6 mm±0.5 mm.

[0020] By adopting the above technical solution, during the desizing process of carbon fiber, the epoxy resin sizing agent on the surface is removed, and the roughness of the carbon fiber surface is increased to facilitate the subsequent sizing agent sizing, thereby improving the bonding force between the sizing agent and the carbon fiber. The carbon fiber is sizing with a sizing agent to introduce active groups on the carbon fiber surface, thereby improving the wettability of the matrix resin and the carbon fiber surface and the chemical cross-linking effect.

[0021] Preferably, the modification method of the modified linear low-density polyethylene is an extrusion grafting method, wherein the linear low-density polyethylene, maleic anhydride monomer, initiator and solvent are blended in a mass ratio of 100:(1-5):(0.02-0.15):10 and then extruded.

[0022] More preferably, the mass ratio of the linear low-density polyethylene, maleic anhydride monomer, initiator and solvent is 100:4:0.1:10.

[0023] More preferably, the initiator is dicumyl peroxide.

[0024] Preferably, the solvent is one or more of acetone, butanone, an acetone aqueous solution and a butanone aqueous solution. More preferably, the solvent is a 2 wt % acetone aqueous solution.

[0025] Preferably, the grafting rate of the modified linear low-density polyethylene is 4%-8%.

[0026] By adopting the above technical solution, the extrusion grafting method is easy to operate in the production process. Linear low-density polyethylene is a non-polar polymer. Grafting maleic anhydride on the molecular chain of linear low-density polyethylene can enhance the compatibility with other components, and is easy to chemically cross-link with the isocyanate group on the surface of the modified carbon fiber, thereby strengthening the interfacial adhesion between the two, which is beneficial to improving the impact strength and tensile strength of the polyethylene material. Preferably, the specific gravity of the linear low-density polyethylene is 0.916-0.920 g / cm 3 , the melt index is 2.6-3.8g / 10min under ASTM D1238 test standard.

[0027] By adopting the above technical solution, the specific gravity is 0.916-0.920g / cm 3 Linear low-density polyethylene with a melt index of 2.6-3.8g / 10min is easier to mold and process during the production of cable materials. At the same time, linear low-density polyethylene has better resistance to environmental stress cracking, impact strength, tensile strength, and tear strength than high-density polyethylene and low-density polyethylene.

[0028] Preferably, the toughening agent is ethylene-methyl acrylate-glycidyl methacrylate terpolymer.

[0029] As an elastomer, the ethylene-methyl acrylate-glycidyl methacrylate terpolymer has a toughening effect on the base resin and improves the impact performance of the material. At the same time, the terpolymer is compatible with polyethylene and ethylene copolymers in any proportion, and there is a strong interface adhesion between each component and the base resin, so that the material still has a high impact strength in a low temperature environment.

[0030] In addition, the ethylene-methyl acrylate-glycidyl methacrylate terpolymer contains epoxy groups, which have a synergistic effect with the isocyanate groups on the modified carbon fiber, thereby improving the compatibility of the two with the matrix resin and improving the impact strength and tensile strength of the material.

[0031] Preferably, the flame retardant comprises aluminum hydroxide, red phosphorus and a flame retardant synergist in a mass ratio of (10-20):(8-12):(2-6).

[0032] More preferably, the flame retardant synergist is one or more of zinc borate, antimony trioxide, and sodium antimonate.

[0033] Preferably, the antioxidant consists of a hindered phenol antioxidant and a phosphite antioxidant.

[0034] Preferably, the mass ratio of the hindered phenol antioxidant to the phosphite antioxidant is 1:1.

[0035] In a second aspect, the present application provides a method for preparing a carbon fiber reinforced low-density flame-retardant polyethylene cable material, comprising the following steps:

[0036] Step 1: Blend linear low-density polyethylene, modified linear low-density polyethylene, flame retardant, toughening agent, antioxidant, lubricant, silicone masterbatch and carbon black

[0037] Step 2: melt-extrude the blended raw materials and modified carbon fiber.

[0038] Preferably, the extrusion temperature of the material is 160-190°C, more preferably, the extrusion temperature of the material is 165-180°C.

[0039] In summary, this application has the following beneficial effects:

[0040] 1. By modifying carbon fiber and linear low-density polyethylene, the wettability between carbon fiber and matrix resin is enhanced, and the interfacial adhesion between the two is increased. The addition of modified carbon fiber can enhance the impact strength and tensile strength of the material, especially increase the electrical properties of the material.

[0041] 2. The toughening agent uses a terpolymer of ethylene-methyl acrylate-glycidyl methacrylate, which has good compatibility with linear low-density polyethylene and can still enhance the impact performance of the material under low-temperature conditions. At the same time, the terpolymer has a synergistic effect with the isocyanate group on the modified carbon fiber, which improves the compatibility of the two with the matrix resin and improves the impact strength and tensile strength of the material. DETAILED DESCRIPTION

[0042] Raw material preparation example

[0043] Preparation example of modified linear low density polyethylene:

[0044] Preparation Example 1-1, a modified linear low-density polyethylene is prepared according to the following method:

[0045] Take 4 kg of maleic anhydride monomer and 0.1 kg of initiator dicumyl peroxide and dissolve them in 10 kg of 2 wt% acetone aqueous solution. 3 , 100kg of linear low-density polyethylene with a melt index of 2.6-3.8g / 10min under the ASTM D1238 test standard is mixed evenly. The mixed raw materials are extruded by a twin-screw extruder at a temperature of 170℃±5℃, a screw speed of 120-130r / min, and a vacuum degree of 0.1MPa. After water cooling, pelletizing, and drying, a modified linear low-density polyethylene with a grafting rate of 7.7% is obtained.

[0046] Preparation Example 1-2, a modified linear low-density polyethylene, is prepared according to the following method:

[0047] Take 1 kg of maleic anhydride monomer and 0.05 kg of initiator dicumyl peroxide and dissolve them in 10 kg of 2 wt% acetone. Mix the solution with a specific gravity of 0.916-0.920 g / cm 3 , 100kg of linear low-density polyethylene with a melt index of 2.6-3.8g / 10min under the ASTM D1238 test standard is mixed evenly. The mixed raw materials are extruded by a twin-screw extruder at a temperature of 170℃±5℃, a screw speed of 120-130r / min, and a vacuum degree of 0.1MPa. After water cooling, pelletizing, and drying, a modified linear low-density polyethylene with a grafting rate of 4.6% is obtained.

[0048] Preparation Example 1-3, a modified linear low-density polyethylene, is different from Preparation Example 1-1 in that, with the masses of other components remaining unchanged, the amount of maleic anhydride monomer used is 0.5 kg, and a modified linear low-density polyethylene with a grafting rate of 3.1% is obtained.

[0049] Preparation Example 1-4, a modified linear low-density polyethylene, differs from Preparation Example 1-1 in that, with the masses of other components remaining unchanged, the amount of maleic anhydride monomer used is 6 kg, and a modified linear low-density polyethylene with a grafting rate of 7.9% is obtained.

[0050] Preparation example of modified carbon fiber:

[0051] Preparation Example 2-1, a modified carbon fiber is prepared according to the following method:

[0052] 1) Preparation of sizing agent: 5 kg of latent crosslinking agent X-NCO was dispersed in 5 kg of aqueous polyethylene wax emulsion, and 0.1 kg of butanone was added and mixed evenly.

[0053] 2) Carbon fiber desizing: In an inert gas atmosphere, the carbon fiber is placed in a desizing furnace at 500-600°C for desizing.

[0054] 3) Carbon fiber sizing: Continuous carbon fiber sizing equipment is used. First, the tension is adjusted to stabilize the unwinding, and then the desized carbon fiber is impregnated and sizing is performed. Finally, the sizing carbon fiber is obtained after drying at 90℃±5℃ and compaction and shaping. The modified carbon fiber with the required length of 6mm±0.5mm is obtained through a cutting table, and the sizing rate is 4.8%.

[0055] Preparation Example 2-2, a modified carbon fiber, differs from Preparation Example 2-1 in that the ratio of the sizing agent is different and is as follows: 1.5 kg of latent crosslinking agent X-NCO, 2.5 kg of aqueous polyethylene wax emulsion, and 0.1 kg of butanone, to obtain a modified carbon fiber with a sizing rate of 1.8%.

[0056] Preparation Example 2-3, a modified carbon fiber, differs from Preparation Example 2-1 in that the ratio of the sizing agent is different and is as follows: 6 kg of latent crosslinking agent X-NCO, 6 kg of aqueous polyethylene wax emulsion, and 0.1 kg of butanone, to obtain a modified carbon fiber with a sizing rate of 4.8%.

[0057] Preparation Example 2-4, a modified carbon fiber, differs from Preparation Example 2-1 in that, in the preparation of the sizing agent in this preparation example, the total mass of the emulsion is kept unchanged while the mass of other components remains unchanged, and an aqueous polyurethane emulsion is used instead of an aqueous polyethylene wax emulsion to obtain a modified carbon fiber with a sizing rate of 4.6%.

[0058] Preparation Example 2-5, a modified carbon fiber, differs from Preparation Example 2-1 in that, in the preparation of the sizing agent in this preparation example, no latent crosslinking agent X-NCO is added to the emulsion, the mass of other components remains unchanged, and a modified carbon fiber with a sizing rate of 4.8% is obtained.

[0059] Example

[0060] Example 1, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, the preparation steps are as follows:

[0061] Weigh and mix according to the formula and mass described in Table 1:

[0062] Table 1 Example 1 Formula

[0063]

[0064] Wherein, the modified linear low-density polyethylene is obtained in Preparation Example 1-1, and the modified carbon fiber is obtained in Preparation Example 2-1.

[0065] After being evenly mixed, the raw materials are reaction-extruded through a twin-screw extruder, wherein the modified carbon fiber is added and extruded through the glass fiber port of the twin-screw extruder, and then the carbon fiber reinforced low-density flame-retardant polyethylene cable material is obtained through water cooling, pelletizing and drying.

[0066] The difference between Examples 2 to 5 is that the raw material ratios are different, as shown in Table 2:

[0067] Table 2 Formula of Examples 1 to 5

[0068]

[0069]

[0070] Examples 1 to 3 use the modified linear low-density polyethylene obtained in Preparation Example 1-1, and Examples 4 and 5 use the modified linear low-density polyethylene obtained in Preparation Example 1-2.

[0071] Among them, Examples 1, 2, and 4 use the modified carbon fiber of Preparation Example 2-1, Example 2 uses the modified carbon fiber of Preparation Example 2-2, and Example 5 uses the modified carbon fiber of Preparation Example 2-3.

[0072] Example 6, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, is different from Example 1 only in that an equal amount of the modified linear low-density polyethylene obtained in Preparation Example 1-3 is used to replace the modified linear low-density polyethylene obtained in Preparation Example 1-1.

[0073] Example 7, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, is different from Example 1 only in that an equal amount of the modified linear low-density polyethylene obtained in Preparation Example 1-4 is used to replace the modified linear low-density polyethylene obtained in Preparation Example 1-1.

[0074] Example 8, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, differs from Example 1 only in that the ethylene-methyl acrylate-glycidyl methacrylate terpolymer toughening agent in Example 1 is replaced by an equal amount of hydrogenated polystyrene-butadiene-styrene triblock copolymer grafted maleic anhydride toughening agent.

[0075] Comparative Example

[0076] Comparative Example 1 is a carbon fiber reinforced low-density flame-retardant polyethylene cable material, which differs from Example 1 in that modified linear low-density polyethylene is not used. An equal amount of linear low-density polyethylene is used to replace the modified linear low-density polyethylene obtained in Preparation Example 1-1; that is, maleic anhydride is not grafted into the molecular chain of the linear low-density polyethylene.

[0077] Comparative Example 2, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, differs from Example 1 in that an equal amount of modified carbon fiber obtained in Preparation Example 2-4 is used to replace the modified carbon fiber obtained in Preparation Example 2-1; that is, no ethylene chain segments are attached to the surface of the modified carbon fiber.

[0078] Comparative Example 3, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, differs from Example 1 in that an equal amount of modified carbon fiber obtained in Preparation Example 2-5 is used to replace the modified carbon fiber obtained in Preparation Example 2-1; that is, no isocyanate groups are attached to the surface of the modified carbon fiber.

[0079] Comparative Example 4, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, differs from Example 1 in that an equal amount of unmodified carbon fiber is used to replace the modified carbon fiber obtained in Preparation Example 2-1.

[0080] Comparative Example 5, a carbon fiber reinforced low-density flame-retardant polyethylene cable material, is different from Example 1 only in that no modified carbon fiber is added.

[0081] Performance testing

[0082] The tensile properties are tested according to GB / T 1040.1-2018 (national standard / determination of tensile properties of plastics);

[0083] Impact performance is tested according to GB / T 1043.1-2008 (national standard / determination of impact performance of plastic simply supported beam);

[0084] The dielectric strength is tested according to GB / T 42125.10-2022 (National Standard / Safety Requirements for Electrical Equipment for Measurement, Control and Laboratory Use Part 10: Special Requirements for Insulation Resistance Measurement and Dielectric Strength Test Equipment);

[0085] The volume resistivity is tested according to GB / T 3048.3-2007 (Test methods for electrical properties of wires and cables (Part 3): Volume resistivity test for semi-conductive rubber and plastic materials).

[0086] The low temperature impact test is used as the criterion for judging whether the product can pass the impact test at -76℃.

[0087] The test results are shown in Table 3:

[0088] Table 3 Test results of embodiments and comparative examples

[0089]

[0090]

[0091] According to Table 3, in combination with Example 1 and Comparative Example 1, it can be seen that the tensile strength and impact strength of Comparative Example 1 are significantly reduced compared with those of Example 1, and the dielectric strength and volume resistivity are also reduced compared with those of Example 1. The reason may be that the modified linear low-density polyethylene containing maleic anhydride is not added in Comparative Example 1, and polyethylene is a non-polar polymer. When it is not modified, it is not easy to crosslink or other reactions occur when it is fused with some polar substances. Polar substances cannot have a good modification effect on polyethylene. Therefore, neither the modified carbon fiber nor the toughening agent can effectively enhance the impact strength, tensile strength and electrical properties of the linear low-density polyethylene in Comparative Example 1.

[0092] Combining Example 1 and Comparative Example 2, it can be seen that the tensile strength, impact strength, dielectric strength and volume resistivity of Comparative Example 2 are all lower than those of Example 1. The reason may be that the sizing agent used for the modified carbon fiber in Comparative Example 2 does not contain aqueous polyethylene wax emulsion, so that the surface of the carbon fiber is not coated with ethylene segments. Although the groups in the aqueous polyurethane emulsion can also cross-link with the modified linear low-density polyethylene to a certain extent, the addition of ethylene segments will result in a second bonding force between the carbon fiber and the linear low-density polyethylene, and the modified carbon fiber and the modified linear low-density polyethylene are more compatible.

[0093] Combining Example 1 and Comparative Example 3, it can be seen that the dielectric strength and volume resistivity of Comparative Example 3 are significantly reduced compared with those of Example 1, and the tensile strength and impact strength are also reduced. The prototype may be that the sizing agent of the modified carbon fiber in Comparative Example 3 does not contain a latent cross-linking agent, and no isocyanate group is introduced on the surface of the modified carbon fiber, so that the modified carbon fiber is not well chemically cross-linked with the modified linear low-density polyethylene.

[0094] Combining Example 1, Comparative Example 4 and Comparative Example 5, it can be seen that the tensile strength, impact strength, dielectric strength and volume resistivity of Comparative Example 4 and Comparative Example 5 are significantly decreased compared with Example 1, especially in Comparative Example 5, the electrical performance is particularly decreased, and the low-temperature impact test failed. The reason may be that the addition of carbon fiber can effectively improve the electrical properties of the required material and can enhance the tensile strength, impact strength, etc. of the material. However, when the carbon fiber is not modified, the surface is chemically inert and has no good interface wettability with the matrix resin. Only by modifying the carbon fiber for the matrix resin system can the tensile strength, impact strength, dielectric strength and volume resistivity of the material be effectively enhanced.

[0095] Combining Example 1 and Example 8, it can be seen that the impact strength of Example 8 is significantly reduced, the low-temperature impact test fails, and the dielectric strength and volume resistivity are slightly reduced. The reason may be that the toughening agent used in Example 8 is a triblock copolymer of hydrogenated polystyrene-butadiene-styrene grafted with maleic anhydride, in which styrene has poor compatibility with the matrix resin and has low impact performance at low temperatures. At the same time, the ethylene-methyl acrylate-glycidyl methacrylate terpolymer can also synergize with the isocyanate group on the surface of the modified carbon fiber to further improve the impact performance of the material.

[0096] Combining Example 1, Example 6 and Example 7, it can be seen that the tensile strength, impact strength, dielectric strength and volume resistivity of Example 6 are all reduced compared with Example 1, and the tensile strength, impact strength, dielectric strength and volume resistivity of Example 7 are not much different from those of Example 1. The reason may be that the amount of maleic anhydride monomer is reduced in Example 6, so that the grafting rate of maleic anhydride on the surface of the modified linear low-density polyethylene decreases, the chemical crosslinking with the isocyanate group on the surface of the carbon fiber is reduced, and the wettability of the modified carbon fiber with the matrix resin is reduced, so that the impact strength, tensile strength, dielectric strength and volume resistivity of the material are all reduced; while in Example 1, the grafting rate of the modified linear low-density polyethylene has been saturated, and the continued addition of maleic anhydride on this basis does not significantly improve the tensile strength, impact strength, dielectric strength and volume resistivity of the material.

[0097] In combination with Examples 1 to 5, it can be seen that the tensile strength, impact strength, dielectric strength and volume resistivity of Examples 2 to 5 are slightly lower than those of Example 1. The reason may be that the proportion of modified linear low-density polyethylene is increased in Example 2, but in Example 1, the combination between modified carbon fiber and modified linear low-density polyethylene has been saturated, and increasing the amount of modified linear low-density polyethylene will not significantly improve the electrical properties of the material; in Example 3, the proportion of inorganic flame retardant is reduced, and the modified linear low-density polyethylene of Preparation Example 2-2 is used. The dielectric strength and volume resistivity of the material decrease with the decrease of sizing rate; in Example 4, the proportion of modified carbon fiber and toughening agent is adjusted, and in Example 5, the proportion of antioxidant, lubricant and silicone masterbatch is adjusted, which has no significant effect on the overall performance of the material.

[0098] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A carbon fiber reinforced low-density flame-retardant polyethylene cable material, characterized in that: The invention comprises the following raw materials in parts by weight: 60 to 80 parts of linear low-density polyethylene, 20 to 40 parts of modified linear low-density polyethylene, 20 to 38 parts of flame retardant, 3 to 8 parts of toughening agent, 1 to 4 parts of antioxidant, 1 to 3 parts of lubricant, 2 to 6 parts of silicone masterbatch, 2 to 5 parts of carbon black, and 5 to 8 parts of modified carbon fiber; the surface of the modified carbon fiber is attached with isocyanate groups and ethylene segments, and the molecular chain of the modified linear low-density polyethylene is grafted with maleic anhydride; The surface of the modified carbon fiber is coated with a sizing agent, and the sizing agent includes a mass ratio of (1-7): (1-6): 0.1 of a latent crosslinking agent X-NCO, an aqueous polyethylene wax emulsion and a dispersant, wherein the molecular structure of the latent crosslinking agent X-NCO is: Where X refers to the aliphatic closed end; The modification steps of the modified carbon fiber are: Carbon fiber desizing: Carbon fiber is desizing in an inert gas atmosphere; Carbon fiber sizing: The desized carbon fiber is subjected to impregnation sizing, drying and compacting, and is shaped and cut to obtain the modified carbon fiber.

2. The carbon fiber reinforced low-density flame-retardant polyethylene cable material according to claim 1, characterized in that: The modification method of the modified linear low-density polyethylene is an extrusion grafting method, which comprises: mixing linear low-density polyethylene, maleic anhydride monomer, initiator and solvent in a mass ratio of 100:(1-5):(0.02-0.15):10 and then extruding them.

3. The carbon fiber reinforced low-density flame-retardant polyethylene cable material according to claim 1, characterized in that: The specific gravity of the linear low-density polyethylene is 0.916-0.920 g / cm 3 , the melt index is 2.6-3.8g / 10min under ASTM D1238 test standard.

4. The carbon fiber reinforced low-density flame-retardant polyethylene cable material according to claim 1, characterized in that: The toughening agent is ethylene-methyl acrylate-glycidyl methacrylate terpolymer.

5. The carbon fiber reinforced low-density flame-retardant polyethylene cable material according to claim 1, characterized in that: The flame retardant comprises aluminum hydroxide, red phosphorus and a flame retardant synergist in a mass ratio of (10-20):(8-12):(2-6).

6. The carbon fiber reinforced low-density flame-retardant polyethylene cable material according to claim 1, characterized in that: The antioxidant is a combination of a hindered phenol antioxidant and a phosphite antioxidant.

7. A method for preparing a carbon fiber reinforced low-density flame-retardant polyethylene cable material according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: blending linear low-density polyethylene, modified linear low-density polyethylene, flame retardant, toughening agent, antioxidant, lubricant, silicone masterbatch and carbon black; Step 2: melt-extrude the blended raw materials and modified carbon fiber.

Citation Information

Patent Citations

  • Carbon fiber strengthened fire-retardant polyethylene composite material

    CN103881184A

  • Halogen-free flame-retardant polyethylene composite material reinforced by surface treated carbon fiber

    CN103881197A

  • Halogen-free flame-retardant polyethylene material reinforced by carbon fiber

    CN103881201A

  • Isocyanate surface modified carbon fiber-polypropylene composite material and preparation method thereof

    CN109810414A